Characterization of the skin microbiome in normal and cutaneous squamous cell carcinoma affected cats and dogs - Jacoba I. Bromfield; Julian Zaugg; Rodney C. Straw; Julia Cathie; Annika Krueger; Debottam Sinha; Janin Chandra; Philip Hugenholtz; Ian H. Frazer (mSphere, 2024)
ABSTRACTHuman cutaneous squamous cell carcinomas (SCCs) and actinic keratoses (AK) display microbial dysbiosis with an enrichment of staphylococcal species, which have been implicated in AK and SCC progression. SCCs are common in both felines and canines and are often diagnosed at late stages leading to high disease morbidity and mortality rates. Although recent studies support the involvement of the skin microbiome in AK and SCC progression in humans, there is no knowledge of this in companion animals. Here, we provide microbiome data for SCC in cats and dogs using culture-independent molecular profiling and show a significant decrease in microbial alpha diversity on SCC lesions compared to normal skin (P ≤ 0.05). Similar to human skin cancer, SCC samples had an elevated abundance of staphylococci relative to normal skin—50% (6/12) had >50% staphylococci, as did 16% (4/25) of perilesional samples. Analysis of Staphylococcus at the species level revealed an enrichment of the pathogenic species Staphylococcus felis in cat SCC samples, a higher prevalence of Staphylococcus pseudintermedius in dogs, and a higher abundance of Staphylococcus aureus compared to normal skin in both companion animals. Additionally, a comparison of previously published human SCC and perilesional samples against the present pet samples revealed that Staphylococcus was the most prevalent genera across human and companion animals for both sample types. Similarities between the microbial profile of human and cat/dog SCC lesions should facilitate future skin cancer research.IMPORTANCEThe progression of precancerous actinic keratosis lesions (AK) to cutaneous squamous cell carcinoma (SCC) is poorly understood in humans and companion animals, despite causing a significant burden of disease. Recent studies have revealed that the microbiota may play a significant role in disease progression. Staphylococcus aureus has been found in high abundance on AK and SCC lesions, where it secretes DNA-damaging toxins, which could potentiate tumorigenesis. Currently, a suitable animal model to investigate this relationship is lacking. Thus, we examined the microbiome of cutaneous SCC in pets, revealing similarities to humans, with increased staphylococci and reduced commensals on SCC lesions and peri-lesional skin compared to normal skin. Two genera that were in abundance in SCC samples have also been found in human oral SCC lesions. These findings suggest the potential suitability of pets as a model for studying microbiome-related skin cancer progression.